The Role of The Teacher's Discipline of The Good Character Development of Early Age Children at Raudlatul Athfal Ma'arif 1 Metro Academic Year 2018/2019 - Leli Fertiliana; Dian Risky Amalia; Nur Laili (SELING: Jurnal Program Studi PGRA, 2019)
Discipline is an important thing that must be instilled in children. Discipline is obedience and obedience to something that has been agreed upon. The role of the teacher is very important in shaping the character of early childhood discipline. Identification of the problems mentioned above, then the formulation of the problem in this study is, How the Role of Teacher Discipline on Good Character Development of Early Childhood in Raudlatul Athfal Ma'arif 1 Metro Academic Year 2018/2019. This research uses a descriptive approach, The triangulation technique research is a technique of finding data in the same data source using different techniques, namely interviews, observation, and documentation. The application of teacher discipline in developing the good character of early childhood has been implemented optimally. The activities are given by the teacher run in accordance with the expectations and achievements of development, which serve as indicators of implementation on aspects of good character. Whereas the good character that is developed by the discipline of teachers in Raudlatul Athfal Ma'arif 1 Metro is to say prayers before and/or after doing something, recognize good/polite and bad behavior, get used to behaving well and say hello and give greetings.